Strategi Humas Dinas Komunikasi Dan Informatika Kota Palembang Dalam Meningkatkan Citra Positif Pemerintah Melalui Media Sosial Instagram - Yunisah, Nasywa; Razzaq, Abdur; Hati, Putri Citra (Komunika : Jurnal Ilmiah Komunikasi, 2025)
This he development of the digital era which demands transparency and speed of information from the government makes managing a positive image a strategic aspect that cannot be ignored. This research aims to analyze the Public Relations strategy of the Palembang City Communication and Informatics Service (Diskominfo) in this effort through the use of Instagram social media, by making the official account management activity @kominfopalembang the main object. Based on the PENCILS Public Relations (PR) Mix Theory, this research uses descriptive qualitative methods. Data collection was carried out through in-depth interviews with key informants, observation of Instagram content, and documentation. The research results show that Diskominfo Public Relations implements most elements of the PENCILS strategy including Publication, Events, News, Community Involvement, Information of Image, Lobbying and Negotiation, and Social Responsibility synergically. The Publication and Information of Image strategy is the main focus in building a modern and transparent government image, supported by News (hoax verification) and Community Involvement to strengthen public trust. The structured and consistent implementation of the PENCILS strategy via Instagram has proven effective in strengthening the positive image of the Palembang City Government, so that it becomes a digital communication model that is able to build trust and closeness with the community.